2016
DOI: 10.1002/pi.5088
|View full text |Cite
|
Sign up to set email alerts
|

Highly transparent flexible polydimethylsiloxane films – a promising candidate for optoelectronic devices

Abstract: In the present work, a siloxane based flexible substrate for optoelectronic applications with improved flexibility and high temperature withstanding capacity has been fabricated and the details are reported. The structural and optical properties of the substrate were characterized and the optical transparency is found to be about 90% − 95% in the visible region. The substrate withstands temperatures up to 300 °C without significant degradation and has a low thermal coefficient of expansion. Fourier transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The ability to synthesize polysiloxanes by polycondensation reactions [13] between cyclic oligosiloxanes and functionalized dichlorosilanes provides a plethora of materials with different chemical structures and mechanical behaviors that can be tuned for different applications. For example, the commonly employed Karstedt's catalyst [17,18] can be used to convert cyclic oligosiloxanes from liquids at room temperature into flexible plastic and gel-like materials that have been used as platforms for optoelectronics [19,20]. With appropriate polar functional groups, polysiloxanes become somewhat hydrophilic, making them useful as adhesives and sealants [11] despite the parent polymers being highly hydrophobic.…”
Section: A Brief History Of Polysiloxanes Including An Overview Of Their Propertiesmentioning
confidence: 99%
“…The ability to synthesize polysiloxanes by polycondensation reactions [13] between cyclic oligosiloxanes and functionalized dichlorosilanes provides a plethora of materials with different chemical structures and mechanical behaviors that can be tuned for different applications. For example, the commonly employed Karstedt's catalyst [17,18] can be used to convert cyclic oligosiloxanes from liquids at room temperature into flexible plastic and gel-like materials that have been used as platforms for optoelectronics [19,20]. With appropriate polar functional groups, polysiloxanes become somewhat hydrophilic, making them useful as adhesives and sealants [11] despite the parent polymers being highly hydrophobic.…”
Section: A Brief History Of Polysiloxanes Including An Overview Of Their Propertiesmentioning
confidence: 99%
“…Substrates, such as SiO 2 /Si and PDMS, are often used in optoelectronic applications. SiO 2 /Si is a rigid substrate having a strong adhesion of 0.45 J/m 2 with graphene . The strong adhesion with the substrate enhances the performance of the optoelectronic devices, such as R and the response speed. , Liu et al demonstrated a silicon-graphene PD with an ultra-high responsivity (R) up to ∼ 10 5 AW –1 and a response time as short as 30 μs .…”
Section: Introductionmentioning
confidence: 99%